2020
DOI: 10.1111/bjep.12367
|View full text |Cite
|
Sign up to set email alerts
|

The role of achievement emotions in primary school mathematics: Control–value antecedents and achievement outcomes

Abstract: Background. Appraisals of control and value are proposed as proximal antecedents of achievement emotions, which, in turn, predict achievement. Relatively few studies have investigated how control and value may interact to determine achievement emotions, or subsequent achievement mediated by emotions. Aim. To examine whether control, value, and their interaction predicted mathematics test score directly, and indirectly, mediated by three salient achievement emotions: enjoyment, boredom, and anxiety. Method. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 42 publications
1
51
0
2
Order By: Relevance
“…Moreover, it is worth noting that detecting different links between boredom and performance in the two examined settings can also shed some light on the reasons underlying some inconsistent results of previous research involving primary-school students, in which boredom was not examined according to different settings (Di Leo et al, 2019;Lichtenfeld et al, 2012;Muis, Psaradellis, et al, 2015;Muis, Ranellucci, et al, 2015;Obergriesser & Stoeger, 2016;Putwain et al, 2018Putwain et al, , 2020Putwain et al, , 2021Raccanello et al, 2019;Robertson et al, 2004;Zaccoletti et al, 2020). Distinguishing homework and tests might have helped to identify another moderator of the relations between boredom and performance, that is, setting, which has been frequently neglected in previous literature (for an exception, see Raccanello et al, 2013).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, it is worth noting that detecting different links between boredom and performance in the two examined settings can also shed some light on the reasons underlying some inconsistent results of previous research involving primary-school students, in which boredom was not examined according to different settings (Di Leo et al, 2019;Lichtenfeld et al, 2012;Muis, Psaradellis, et al, 2015;Muis, Ranellucci, et al, 2015;Obergriesser & Stoeger, 2016;Putwain et al, 2018Putwain et al, , 2020Putwain et al, , 2021Raccanello et al, 2019;Robertson et al, 2004;Zaccoletti et al, 2020). Distinguishing homework and tests might have helped to identify another moderator of the relations between boredom and performance, that is, setting, which has been frequently neglected in previous literature (for an exception, see Raccanello et al, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…For example, in mathematics boredom is linked to academic performance as evidenced by small to moderate negative correlations (ranging from À.16 to À.42) as well as by small positive correlations (Di Leo et al, 2019;Lichtenfeld et al, 2012;Muis, Psaradellis, Lajoie, Di Leo, & Chevrier, 2015;Putwain et al, 2018;Raccanello et al, 2019). In other cases, researchers found that achievement predicted boredom but not vice versa (Putwain et al, 2021;Putwain, Wood, & Pekrun, 2020). For science learning, small negative correlations emerged (Obergriesser & Stoeger, 2016).…”
Section: Appraisals and Outcomes Of Boredommentioning
confidence: 99%
“…In secondary school students, Ahmed et al (2013) found unique statistically significant relations with mathematics achievement for enjoyment (positively), and boredom and anxiety (negatively). However, Raccanello et al (2019; elementary school students) and Putwain et al (2020;primary school students) found that only enjoyment and anxiety, but not boredom, remained statistically significant unique predictors of subsequent mathematics achievement.…”
Section: Achievementmentioning
confidence: 87%
“…Emotions of progress (Pekrun & Stephens, 2010) emphasize not only consequential emotions, but also emotions related to activities such as enjoyment of learning, fatigue during training, and anger at homework requirements. Academic excitement is directly related to academic achievement (Bhansali & Sharma, 2020), which affects student performance and subsequently enhances learning and academic achievement (Putwain, Schmitz, Wood & Pekrun, 2020). Research has confirmed the two-way relationship between academic excitement and academic achievement.…”
Section: Introductionmentioning
confidence: 92%